Supercomputing Frontiers: 4th Asian Conference, SCFA 2018, Singapore, March 26-29, 2018, Proceedings - Yokota, Rio; Wu, Weigang (Theoretical Computer Science and General Issues, 2018)
artificial intelligence; big data; cloud computing; communication; computer architecture; computer science; computer systems; data management; databases; hardware; High-Performance Computing (HPC); information management; map-reduce; processors; programming languages; semantics; wireless telecommunication systems